2021
DOI: 10.1371/journal.pone.0256479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peer counselling on acceptance of modern contraceptives among female refugee adolescents in northern Uganda: A randomised controlled trial

Abstract: Background The unmet need for contraceptives among refugee adolescents is high globally, leaving girls vulnerable to unintended pregnancies. Lack of knowledge and fear of side effects are the most reported reasons for non-use of contraceptives amongst refugee adolescents. Peer counselling, the use of trained adolescents to offer contraceptive counselling to fellow peers, has showed effectiveness in increasing use of contraceptives in non-refugee adolescent resarch. Objective To determine the effect of peer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…There is a plethora of studies published to date which focus on the sexual and reproductive health of refugee populations in Uganda [11][12][13][14][15][16][17][18][19] and Ugandan populations [20][21][22][23][24][25][26][27][28]. However, to our knowledge, there are no published studies focused on the sexual and reproductive health of both refugee and host populations, which is important to study given that both these populations are often living in close proximity to each other and have access to the same services, though experience different health outcomes [29].…”
Section: Introductionmentioning
confidence: 99%
“…There is a plethora of studies published to date which focus on the sexual and reproductive health of refugee populations in Uganda [11][12][13][14][15][16][17][18][19] and Ugandan populations [20][21][22][23][24][25][26][27][28]. However, to our knowledge, there are no published studies focused on the sexual and reproductive health of both refugee and host populations, which is important to study given that both these populations are often living in close proximity to each other and have access to the same services, though experience different health outcomes [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the present review, 10 studies utilized counselling interventions as strategies for improving modern family services uptake and decreasing myths and misconceptions about modern contraceptives. Among these studies, 2 from an article by Bakesiima and colleagues, 2021, reported that peer counselling improved modern contraceptives acceptance and dispelled myths and misconceptions about modern contraceptives among adolescent girls aged 15–19 years ( 57 ). Furthermore, 8 studies from 5 articles reported that groups or couples counselling only, and counselling combined with different SRH interventions (including CHWs, economic support and YFHS) increased modern family planning services uptake and utilization among young women ( 34 , 36 38 , 55 ) (see Table 2 for details of the counselling multicomponent interventions).…”
Section: Resultsmentioning
confidence: 99%
“…We developed a structured questionnaire by reviewing the existing literature with instruments on the knowledge and practice of SRHR among adolescents and teenagers in LMICs. We complied with questions from the Demographic and Health Survey in Uganda20 and other studies conducted mainly in sub-Saharan countries 41–43 46–48. Questions included basic sociodemographic characteristics, SRHR knowledge and perceptions, sexual behaviour, and vendor usage (online supplemental material S2).…”
Section: Methodsmentioning
confidence: 99%